2006
DOI: 10.1007/s11548-006-0059-z
|View full text |Cite
|
Sign up to set email alerts
|

OncoTREAT: a software assistant for cancer therapy monitoring

Abstract: Object Cancer is one of the leading causes of death worldwide and therapy options are often associated with severe stress for the patient and high costs. Therefore, precise evaluation of therapy success is essential. Material and methods In the framework of the VICORA research project (Virtual Institute for Computer Assistance in Clinical Radiology), a software application L. Bornemann (B) · was developed to support the radiologist in evaluating the response to tumor therapy. The application provides follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Smaller adjacent structures of similar density are excluded from the segmentation by morphological operations. A more detailed description of the algorithm is given by Bornemann et al [12].…”
Section: Software Algorithmmentioning
confidence: 99%
“…Smaller adjacent structures of similar density are excluded from the segmentation by morphological operations. A more detailed description of the algorithm is given by Bornemann et al [12].…”
Section: Software Algorithmmentioning
confidence: 99%
“…contrast media, maximally 130 ml (Imeron 300®, Bracco Altana Pharma GmbH, Konstanz, Germany), and 800 ml of diluted Barium sulfate orally (Barilux®, Sanochemia Diagnostics International, Neuss, Germany). [14,15]. A total of 227 suspicious, enlarged lymph nodes (median n=4 lymph nodes per patient, range 1-10) were selected and marked before evaluation by one of the co-authors and independently evaluated by two radiologists.…”
Section: Study Design Scan Techniquementioning
confidence: 99%
“…Computer simulations have shown that volume measurements are more accurate than RECIST for classifying response to therapy [19]. But the reliability of conclusions drawn from imaging phantoms and simulations is modest because they are derived from ideal conditions lacking the spectrum of complexity encountered under clinical conditions.…”
Section: Discussionmentioning
confidence: 99%